2022
DOI: 10.3389/fcvm.2022.1016081
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GLS as a cuproptosis-related diagnosis gene in acute myocardial infarction

Abstract: Acute myocardial infarction (AMI) has the characteristics of sudden onset, rapid progression, poor prognosis, and so on. Therefore, it is urgent to identify diagnostic and prognostic biomarkers for it. Cuproptosis is a new form of mitochondrial respiratory-dependent cell death. However, studies are limited on the clinical significance of cuproptosis-related genes (CRGs) in AMI. In this study, we systematically assessed the genetic alterations of CRGs in AMI by bioinformatics approach. The results showed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 66 publications
1
18
0
Order By: Relevance
“…It has been demonstrated that GLS is an anti-cuproptosis gene [ 45 ]. GLS has been identified as a genetic marker for the diagnosis of acute myocardial infarction [ 46 ] and has been less studied in other diseases, but results have been published in cancers such as glioma [ 47 ], breast cancer [ 48 ] and liver cancer [ 49 ].However, these two marker genes have not been studied in the subject of prematurity. It is worth our attention that these genes are related to human chromosome 2, which provides a direction for future genetic screening of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GLS is an anti-cuproptosis gene [ 45 ]. GLS has been identified as a genetic marker for the diagnosis of acute myocardial infarction [ 46 ] and has been less studied in other diseases, but results have been published in cancers such as glioma [ 47 ], breast cancer [ 48 ] and liver cancer [ 49 ].However, these two marker genes have not been studied in the subject of prematurity. It is worth our attention that these genes are related to human chromosome 2, which provides a direction for future genetic screening of embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few bioinformatics studies on non-tumour diseases have reported that the expression of some copper-induced death-related genes changed in IgA nephropathy, Alzheimer's disease, in ammatory bone disease, endometriosis, and acute myocardial infarction. These include CDKN2A, GLS, MTF1, PDHB, PDHA1, DLAT, DLD, LIPT1, LIAS and FDX1 [29][30][31][32][33][34], of which FDX1 is a key gene [35][36]. However, there are no detailed studies on copper-induced death in the aforementioned diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We combined the top 10 potential hub genes and the genes involved in the most significant module to identify the overlapping genes, which were ultimately regarded as hub genes related to necroptosis. The correlations of the hub genes were analyzed using the Spearman correlation in the “corrplot” package, and differences with p < 0.05 were considered statistically significant [ 29 ].…”
Section: Methodsmentioning
confidence: 99%